Pendampingan Pembuatan Alat Pendeteksi Embrio Telur Itik Pada Kelompok Tani Meri Rejeki Desa Rejosopinggir Tembelang Jombang - Dyah Ayu Sri Hartanti; Khotim Fadhli; M Nouval Analis Blonos; Moch Wildan Ramadhan; Mita Julia Putri (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The community service carried out aims to train the community to make appropriate technology tools in the form of a simple granular fertilizer applicator on dry land to increase fertilization efficiency. Service activities in Rejosopinggir Village, Tembelang District, Jombang Regency, East Java. The implementation of community service activities will be carried out in November 2021. The implementation of community service activities uses the Asset Based Community Development (ABCD) method, which is an approach model in community development. This approach is an approach that leads to the understanding and internalization of assets, potential, strengths, and their utilization independently and maximally. The community is one of the assets for a region that can participate in filling development. Communities in village areas can collaborate based on the existing potential, both human resources and natural resources. The activity was carried out in collaboration with groups and partners. This implementation was participatory, group teams and partners join involved in each activity. Activities carried out in the form of socialization and group discussion through one meeting in the form of face to face. Based on the community service activities that have been carried out, it can be concluded that a simple granular fertilizer applicator can be used to increase time and labor efficiency for fertilization and farmers gain knowledge to utilize unused used materials. Suggestions for further service are that the community can implement and practice what has been socialized and this simple granular fertilizer applicator can be developed into a better tool.